PRAKTIK BUDIDAYA JAMUR TIRAM DENGAN MENGGUNAKAN SISTEM TRADISIONAL DI DESA LEGUNDI - Baharuddin Mohammad L; Wahyu Ramadhan; Yuzy Febryanti Ardi; M. Wahyu Rahmasaputra; Anggraheny Sulistyana; Nathanael Hizkia R; Taufikkurahman Taufikkurahman (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Mushrooms are a type of fibrous plant that can be used as a favorite food ingredient for Indonesian people. White oyster mushroom (Pleurotusostreatus) is called oyster mushroom because it is shaped like an oyster shell, white semicircle. Usually white oyster mushrooms live in the wild and are often found on rotten wood trunks, so oyster mushrooms are often called wood mushrooms. Fungal plants can be classified into spore plants, have a plasma nucleus, but do not have chlorophyll (no green leaf substance). This activity was carried out at the oyster mushroom cultivation center owned by Mr. Doni which was located in Jembatan Hamlet, Legundi Village, Bantaran District, Probolinggo Regency, East Java Province in June 2022. The method used in this study was qualitative descriptive using observations and interviews. From this research, it is hoped that 1) the community is expected to be motivated as mushroom farmers in Legundi Village, but there is a problem that the community cannot accept existing innovations before the innovation is successful. 2) indirectly can contribute knowledge to the community about mushroom cultivation. 3) make mushroom UMKM products in Legundi Village as superior products.